Glutathione S-transferase gene family analysis and enzymatic properties of three selenium-responsive members from selenium hyperaccumulator Cardamine hupingshanensis - Jingyu Xie; Yushan Chen; Jingyi Liu; Xinying Gao; Xinyi Liang; Anjun Chen; Zhixin Xiang; Shengcai Chen; Zhi Hou; Yanke Lu; Qiaoyu Tang; Yifeng Zhou (Plant Science, 2026)

Engineering carbon dots with amplified peroxidase-mimetic activity for dual-modal colorimetric-photothermal sensing of organophosphorus and carbamate pesticides - Na Gao; Yajuan Zhao; Yuhan Huang; Yanke Zhou; Linlin Yang; Liguo Ji; Hao Zhu; Wenjie Ren; Guangjie He (Analytica Chimica Acta, 2026)

Sulfotransferases in Cardamine hupingshanensis: Identification, expression, and regulatory role in selenium metabolism under selenium stress - Jing Xiao; Qian Yuan; Anjun Chen; Xixi Zeng; Yanke Lu; Zhixin Xiang; Zhi Hou; Qiaoyu Tang; Yifeng Zhou (Plant Science, 2025)

Role of ocean-atmosphere interaction in intraseasonal variability of summer rainfall over the Indo–Northwest Pacific - Yang Wang; Zhen-Qiang Zhou; Renhe Zhang; Yanke Tan (Climate Dynamics, 2024)

Gene identification, expression analysis, and molecular docking of SAT and OASTL in the metabolic pathway of selenium in Cardamine hupingshanensis - Yushan Chen; Yao Li; Guoqiang Luo; Cihang Luo; Zhijing Xiao; Yanke Lu; Zhixin Xiang; Zhi Hou; Qiang Xiao; Yifeng Zhou; Qiaoyu Tang (Plant Cell Reports, 2024)
Key message Identification of selenium stress-responsive expression and molecular docking of serine acetyltransferase (SAT) and O -acetyl serine (thiol) lyase (OASTL) in Cardamine hupingshanensis. Abstract A complex coupled with serine acetyltransferase (SAT) and O -acetyl serine (thiol) lyase (OASTL) is the key enzyme that catalyzes selenocysteine (Sec) synthesis in plants. The functions of SAT and OASTL genes were identified in some plants, but it is still unclear whether SAT and OASTL are involved in the selenium metabolic pathway in Cardamine hupingshanensis . In this study, genome-wide identification and comparative analysis of ChSAT s and ChOASTL s were performed. The eight ChSAT genes were divided into three branches, and the thirteen ChOASTL genes were divided into four branches by phylogenetic analysis and sequence alignment, indicating the evolutionary conservation of the gene structure and its association with other plant species. qRT-PCR analysis showed that the ChSAT and ChOASTL genes were differentially expressed in different tissues under various selenium levels, suggesting their important roles in Sec synthesis. The ChSAT1;2 and ChOASTLA1;2 were silenced by the VIGS system to investigate their involvement in selenium metabolites in C. hupingshanensis . The findings contribute to understanding the gene functions of ChSAT s and ChOASTL s in the selenium stress and provide a reference for further exploration of the selenium metabolic pathway in plants.

Comparison of two filter approaches for characterizing boreal summer intraseasonal oscillation - Yang Wang; Zhen-Qiang Zhou; Renhe Zhang; Yanke Tan (Atmospheric Research, 2024)

Interannual variability of surface air temperature over indochina peninsula during summer monsoon onset - Meiru Zhang; Zhen-Qiang Zhou; Renhe Zhang; Yanke Tan; Min Wen (Climate Dynamics, 2023)

Involvement of MEM1 in DNA demethylation in Arabidopsis - Yanke Lu; Jie Dai; Liu Yang; Yumei La; Shaoxia Zhou; Sheng Qiang; Qianqian Wang; Feng Tan; Yufeng Wu; Weiwen Kong; Honggui La (Plant Molecular Biology, 2020)

Remote impact of North Atlantic sea surface temperature on rainfall in southwestern China during boreal spring - Gang Li; Jiepeng Chen; Xin Wang; Xia Luo; Daoyong Yang; Wen Zhou; Yanke Tan; Hongming Yan (Climate Dynamics, 2018)